Mitochondria are the main source and one of the targets of Pb (lead)-induced oxidative stress in the yeast Saccharomyces cerevisiae - Sousa, Cátia A. (2017)
The yeast Saccharomyces cerevisiae is a useful model organism for studying lead (Pb) toxicity. Yeast cells of a laboratory S. cerevisiae strain (WT strain) were incubated with Pb concentrations up to 1,000 μmol/l for 3 h. Cells exposed to Pb lost proliferation capacity without damage to the cell membrane, and they accumulated intracellular superoxide anion (O2 .−) and hydrogen peroxide (H2O2). The involvement of the mitochondrial electron transport chain (ETC) in the generation of reactive oxygen species (ROS) induced by Pb was evaluated. For this purpose, an isogenic derivative ρ0 strain, lacking mitochondrial DNA, was used. The ρ0 strain, without respiratory competence, displayed a lower intracellular ROS accumulation and a higher resistance to Pb compared to the WT strain. The kinetic study of ROS generation in yeast cells exposed to Pb showed that the production of O2 .− precedes the accumulation of H2O2, which is compatible with the leakage of electrons from the mitochondrial ETC. Yeast cells exposed to Pb displayed mutations at the mitochondrial DNA level. This is most likely a consequence of oxidative stress. In conclusion, mitochondria are an important source of Pb-induced ROS and, simultaneously, one of the targets of its toxicity.